A comparative study of the credit card market dynamics in Mexico and Brazil - Cordeau-Andrews, Suzanne (2016)
This research analyzes and compares the attractiveness of the Brazilian and Mexican credit card markets from a financial firm’s perspective. The market dynamics in Latin America’s two economic powerhouses are fleshed out with qualitative and quantitative data, using a strategic framework to structure the analysis. Since its adoption by both countries in 1956, credit card usage has experienced many years of double digit growth. However, penetration levels remain low compared with most developed countries. Brazil has a more developed credit card infrastructure, with more potential profit, and issuers might face fewer competitive challenges.  Alternatively, Mexico, is witnessing a more favorable economy, a friendlier business and regulatory environment, combined with fewer financial products that compete with the credit card. Therefore, this paper concludes that Brazil and Mexico both offer market opportunities for credit card companies that can navigate the different technological, demographic, macroeconomic, and regulatory shifts in each country.